Measurement of the neutrino oscillation parameters sin²θ23, Δm²32, sin²θ13, and δCP in neutrino and antineutrino oscillation at T2K - Duffy, K (2016)
The T2K experiment is a long-baseline neutrino oscillation experiment, in which a muon neutrino beam is directed over a 295 km baseline from the J-PARC facility to the Super-Kamiokande detector. This allows neutrino oscillation to be studied in two channels: disappearance of νμ and appearance of νe. The T2K beam can be run either in neutrino or antineutrino configuration, for a neutrino beam which is predominantly composed of νμ or anti ¯νμ respectively. This thesis presents the first oscillation analysis to combine neutrino-mode and antineutrino-mode data sets, giving the first ever sensitivity to the CP-violating phase δCP from T2K data alone, as well as the most precise T2K measurement of the other neutrino oscillation parameters. The analysis uses a Markov Chain Monte Carlo method to construct a sample from the Bayesian posterior distribution, from which the oscillation parameters of interest and their uncertainties are estimated. Data samples from the T2K near detector, ND280, are fit simultaneously with data from the far detector in order to reduce the uncertainty in the far-detector prediction. When fitting the T2K data alone, the best-fit oscillation parameter values are sin2 θ23= 0.519+0.031-0.059, sin2 θ13= 0.0257+0.0106-0.0440, Δm232= 2.54+0.12-0.10 × 10-3eV2,and δCP=-1.91 rad. The 90% credible interval for δCP excludes values around π/2: δCP ∉ [0.38, 2.60] rad. When fitting the T2K data with a constraint on sin2 θ13 from measurements by reactor experiments, the best-fit oscillation parameter values are sin2 θ23= 0.519+0.061-0.029, sin2 θ13= +0.0014-0.0014, Dm232= 2.54+0.12-0.12 × 10-3eV2, and δCP=-1.72 rad. The 90% credible interval for δCP contains values δCP ∈ [-3.10,-0.17] rad, excluding the CP-conserving values 0 and ±π at 90% probability.